Efficient Catalytic Reduction of Organic Pollutants Using Nanostructured CuO/TiO2 Catalysts: Synthesis, Characterization, and Reusability - Mariyem Abouri; Abdellah Benzaouak; Fatima Zaaboul; Aicha Sifou; Mohammed Dahhou; Mohammed Alaoui El Belghiti; Khalil Azzaoui; Belkheir Hammouti; Larbi Rhazi; Rachid Sabbahi; Mohammed M. Alanazi; Adnane El Hamidi (Inorganics)
The catalytic reduction of organic pollutants in water is a critical environmental challenge due to the persistent and hazardous nature of compounds like azo dyes and nitrophenols. In this study, we synthesized nanostructured CuO/TiO2 catalysts via a combustion technique, followed by calcination at 700 °C to achieve a rutile-phase TiO2 structure with varying copper loadings (5–40 wt.%). The catalysts were characterized using X-ray diffraction (XRD), attenuated total reflectance-Fourier transform infrared (ATR–FTIR) spectroscopy, thermogravimetric analysis-differential thermal analysis (TGA–DTA), UV-visible diffuse reflectance spectroscopy (DRS), and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM–EDS). The XRD results confirmed the presence of the crystalline rutile phase in the CuO/TiO2 catalysts, with additional peaks indicating successful copper oxide loading onto TiO2. The FTIR spectra confirmed the presence of all the functional groups in the prepared samples. SEM images revealed irregularly shaped copper oxide and agglomerated TiO2 particles. The DRS results revealed improved optical properties and a decreased bandgap with increased Cu content, and 4-Nitrophenol (4-NP) and methyl orange (MO), which were chosen for their carcinogenic, mutagenic, and nonbiodegradable properties, were used as model organic pollutants. Catalytic activities were tested by reducing 4-NP and MO with sodium borohydride (NaBH4) in the presence of a CuO/TiO2 catalyst. Following the in situ reduction of CuO/TiO2, Cu (NPs)/TiO2 was formed, achieving 98% reduction of 4-NP in 480 s and 98% reduction of MO in 420 s. The effects of the NaBH4 concentration and catalyst mass were investigated. The catalysts exhibited high stability over 10 reuse cycles, maintaining over 96% efficiency for MO and 94% efficiency for 4-NP. These findings demonstrate the potential of nanostructured CuO/TiO2 catalysts for environmental remediation through efficient catalytic reduction of organic pollutants.